2009
DOI: 10.1111/j.1600-0404.1990.tb01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal neuropathy preceding chronic inflammatory demyelinating polyradiculoneuropathy by several years

Abstract: We report three patients who exhibited an unusual clinical course of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) in which mononeuropathic limb weakness developed 2,11 and 23 years, respectively, before the development of generalized polyradiculoneuropathy. The eventual diagnosis remained uncertain until other causes of neuropathy were excluded, and the clinical disorder progressed to involve the other limbs. Focal or regional variants of CIDP suggest that the pathologic, and perhaps the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…We identified 82 prior reports of patients with an initially pure upper‐limb form of asymmetric CIDP, or L‐SS, in 25 publications,3, 5–10, 12, 14, 17–20, 23, 28, 29, 31–33, 35, 36, 38–40, 42 including Lewis et al's 5 original patients (1982) 14. A summary of the clinical, biologic, immunologic, histologic, radiologic, and therapeutic characteristics of the 82 patients is provided in Table 3 (see supplementary file).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 82 prior reports of patients with an initially pure upper‐limb form of asymmetric CIDP, or L‐SS, in 25 publications,3, 5–10, 12, 14, 17–20, 23, 28, 29, 31–33, 35, 36, 38–40, 42 including Lewis et al's 5 original patients (1982) 14. A summary of the clinical, biologic, immunologic, histologic, radiologic, and therapeutic characteristics of the 82 patients is provided in Table 3 (see supplementary file).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 36 other cases of L‐SS, with asymmetric lower‐limb, or mixed, simultaneous upper‐ and lower‐limb onset, from 12 studies,2, 9, 19, 23, 25, 27, 31, 36, 38–41 as shown in Tables 5 and 6. To these, we added 2 new patients from our clinic who presented with this form of L‐SS.…”
Section: Resultsmentioning
confidence: 99%
“…Focal CIDP has also been reported with symptoms remaining restricted to one focal region for a prolonged period of time, 15 but may also precede the development of diffuse CIDP. 35 Focal sensory CIDP has been reported restricted to one upper limb for 30 years. 36 …”
Section: Cidp Phenotypic Variantsmentioning
confidence: 99%
“…Patients can present initially with involvement of single nerves that progress to confluent and symmetrical involvement. 94, 98 Up to one-half of patients with MADSAM may evolve into a typical pattern of generalized CIDP. 12 Many patients experience pain and paresthesias.…”
Section: Multifocal Acquired Demyelinating Sensory and Motor (Madsam)mentioning
confidence: 99%